No country for young women farmers: A situation analysis for India - Narayanan, Sudha; Srinivasan, Sharada (Practical Action Publishing Ltd, 2025)
In spite of their significant role in agriculture in India, women lack recognition as farmers and face structural barriers related to land ownership, access to resources and markets, and mobility, which are associated with high levels of gender discrimination and gender-based violence (Panda and Agarwal 2005; UNODC 2018). There is a stark absence of an intersectional analysis (based on age, disability, class, education) in the otherwise substantial body of scholarship on women in agriculture and the gender barriers that they encounter, tending instead to generalize a communal female experience. This lacuna is apparent in this current review of the situation of young women farmers in India. At the policy level, this silence is even more deafening; the predicament of young women farmers is something of a policy desert.